Model Silabus Nosional Bagi Pengajaran Bahasa Arab - Farihatul Husniyah (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2017)
The syllabus is considered as one of the main components in the learning process, it contains lists of activities that should be done at the end of the programs and reaches the purpose of language learning. There are many kinds of syllabuses, one of them is Notional Syllabus. It is coupled with a communicative teaching approach make clear benefit in learning and using language. This syllabus is more suitable for learning language for specific purposes. But the creative teachers can bring the notional syllabus into their class, with some considerations, and make the learning process more interesting. This article describes the application of a notional syllabus in Arabic teaching and learning.